(untitled) (KULT_online, 2012)
Noblemen, pilgrims, artists, intellectuals, merchants, and tourists from the German-speaking countries have been drawn to Venice for more than a thousand years. In a study well worth the reading, historian Klaus Bergdolt describes the various relations between the city of canals, Germans, and Austrians, ’from Medieval Emperors to Thomas Mann.’ His study is based on a large assembly of letters, chronicles, diaries, and literary excerpts which, taken together, allow the reader to share the personal experience of the travellers to Venice.